Integration process of fermentation and liquid biphasic flotation for lipase separation from Burkholderia cepacia - Sankaran, Revathy; Show, Pau Loke; Lee, Sze Ying; Yap, Yee Jiun; Ling, Tau Chuan (Elsevier, 2018)
Liquid Biphasic Flotation (LBF) is an advanced recovery method that has been effectively applied for biomolecules extraction. The objective of this investigation is to incorporate the fermentation and extraction process of lipase from Burkholderia cepacia using flotation system. Initial study was conducted to compare the performance of bacteria growth and lipase production using flotation and shaker system. From the results obtained, bacteria shows quicker growth and high lipase yield via flotation system. Integration process for lipase separation was investigated and the result showed high efficiency reaching 92.29% and yield of 95.73%. Upscaling of the flotation system exhibited consistent result with the lab-scale which are 89.53% efficiency and 93.82% yield. The combination of upstream and downstream processes in a single system enables the acceleration of product formation, improves the product yield and facilitates downstream processing. This integration system demonstrated its potential for biomolecules fermentation and separation that possibly open new opportunities for industrial production.